Monitoring and evaluating urban development programs : a handbook for program managers and researchers - Bamberger, Michael; Hewitt, Eleanor (Washington, D.C., U.S.A. : World Bank, 1986)
This is a comprehensive but easily understood handbook for urban policy makers, managers and evaluation practitioners in developing countries. It provides guidance on all stages of the design and implementation of a monitoring and evaluation system and presents the main options with respect to scope, key research issues and organization. Monitoring and evaluation systems are described which can be applied to both individual projects and to integrated multi-component urban development programs. All of the methods described in this handbook have been field tested, most but not all of them as part of World Bank projects.
Includes bibliographical references: p. 257-263.
oo 10/04/2019
Loans
Keywords: City planning